Performances of Metal Oxides Supported in Monolith for Combined SO2/NOx removal from Flue Gas - Kiman, S.; Mohammed, H. D.; Aliyu, N. B.; Usman , T. H.; Kayode, D. B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
The emission of acid gases such SO2 and NOx have detrimental effects on human beings and the environment hence, removing them from flue gas in a dry adsorption process is desirable. In this work, carbon monolith was synthesized with various metals consisting of CeO2, Co3O4, V2O5, and CuO by deposition precipitation, hydrothermal and wet pore volume impregnation synthesis techniques. The fixed bed adsorption activity test was carried out with flue gas production by coal burning. Furthermore, the breakthrough curves of the adsorbents were investigated where the adsorbent developed via hydrothermal technique with Co3O4 metal oxide termed as HM-Co3O4 /CM displayed higher adsorption capacity for both SO2 (103.9 mg/g) and NOx and (106.6 mg/g). The Langmuir model can best describe the experimental data based on the correlation coefficient and separation factor results. These results implied that the developed adsorbent can be potentially used in the industry for flue gas cleaning.